Strengthening Student Punctuality Discipline through The Ketarunaan Extracurricular Program at SMK Gula Rajawali, Madiun City - Mahardhika, Itang Enrico Pradana; Sumardjoko, Bambang; Fathoni, Achmad; Haryanto, Sigit (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study analyzes the influence of the Ketarunaan extracurricular program on improving students’ punctuality at SMK Gula Rajawali, Kota Madiun. Punctuality is a fundamental aspect of character development that is essential for academic, social, and professional success. However, a lack of timeliness remains a persistent challenge in educational environments. The Ketarunaan program at this school is believed to hold significant potential in instilling discipline through its structured and distinctive activities. This research adopts a qualitative approach to explore how the implementation of the Ketarunaan program affects students' punctual behavior. The conceptual framework highlights three main mechanisms through which the program operates. First, the consistent practice of morning assemblies and marching routines trains students to arrive on time. Second, self-awareness training encourages students to understand the value of time and the consequences of indiscipline, fostering internal motivation. Third, a participatory approach and habituation across all Ketarunaan activities actively engage students, making them more motivated to comply with time-related rules. These three pillars synergistically contribute to the enhancement of students’ punctuality. This study aims to provide a comprehensive understanding of the effectiveness of the Ketarunaan program as a strategy for strengthening time discipline and to offer valuable insights for the development of similar programs in other educational institutions.